Aceitabilidade, adesão e cumprimento das orientações médico-científicas sobre a Covid-19 em uma unidade básica de saúde do município de Bayeux-PB - Guimarães, Romulo Brito (2022)
The new coronavirus pandemic has changed the way of coping with diseases, given its harmful effects on health and the lack of effective medicines and vaccines to eliminate the infection or fight its spread. Therefore, there was a need to implement prevention and control measures that could be practiced by all segments of the population, such as frequent hand washing, use of a face mask and physical distancing. However, adherence to these measures was severely hampered in Brazil due to the high flow of true and false information, as well as the lack of intergovernmental articulation. Despite this difficulty, the Unified Health System, through primary care, has been facing the pandemic crisis, acting in the line of protection, prevention and combating COVID-19. The objective of this study is to analyze the perception and practice of prevention and control measures against COVID-19 by families assisted by a basic health unit in the municipality of Bayeux - PB. This is an observational study with a quantitative approach, based on the collection of primary data with 85 families enrolled in the aforementioned health unit, through interviews based on a structured questionnaire. Based on the responses of each family, data were tabulated and statistical analyzes were performed using the Statistical Package for the Social Sciences (SPSS) software, version 26.0 for Windows. All the results presented were not statistically significant (p > 0.05). The dissertation presents as products an original scientific article and an illustrated booklet for elderly people in primary care regarding the prevention of COVID-19.